Carbofuran removal in continuous-photocatalytic reactor: Reactor optimization, rate-constant determination and carbofuran degradation pathway analysis. Issue 5 (4th May 2017) - Vishnuganth, M. A.; Remya, Neelancherry; Kumar, Mathava; Selvaraju, N.
ABSTRACT: Carbofuran (CBF) removal in a continuous-flow photocatalytic reactor with granular activated carbon supported titanium dioxide (GAC-TiO2 ) catalyst was investigated. The effects of feed flow rate, TiO2 concentration and addition of supplementary oxidants on CBF removal were investigated. The central composite design (CCD) was used to design the experiments and to estimate the effects of feed flow rate and TiO2 concentration on CBF removal. The outcome of CCD experiments demonstrated that reactor performance was influenced mainly by feed flow rate compared to TiO2 concentration. A second-order polynomial model developed based on CCD experiments fitted the experimental data with good correlation ( R 2 ∼ 0.964). The addition of 1 mL min −1 hydrogen peroxide has shown complete CBF degradation and 76% chemical oxygen demand removal under the following operating conditions of CBF ∼50 mg L −1, TiO2 ∼5 mg L −1 and feed flow rate ∼82.5 mL min −1 . Rate constant of the photodegradation process was also calculated by applying the kinetic data in pseudo-first-order kinetics. Four major degradation intermediates of CBF were identified using GC-MS analysis. As a whole, the reactor system and GAC-TiO2 catalyst used could be constructive in cost-effective CBF removal with no impact to receiving environment through getaway of photocatalyst.